Breaking through : stories and best practices from companies that help women succeed - Liautaud, Martine, 1950- (Wiley, 2016)
"When women succeed, we all win. Breaking Through explores the mentoring relationship, and unravels its effects on women, businesses, society, and the economy. In 2010, author Martine Liautaud founded the Women Business Mentoring Initiative (WBMI) to support women entrepreneurs with the targeted advice and personalized guidance that can only come from a mentor. In late 2015, she set up the Women Initiative Foundation to broaden her action in favor of women in the business world. This book encapsulates the WBMI mission and other similar experiences inside international and US corporations, showing how mentoring and sponsorship can take many forms—and how each form benefits women in business. Through evidence-based narratives, you'll learn what real women have gained from both sides of the dynamic, and why they credit mentoring with the strength of their business success. These stories show how mentoring yields increased efficiency, improved financials, more effective management, increased innovation, a broader talent pool, and increased revenues, and how helping women succeed in business leads to increased philanthropy and improves community sustainability. Gender equality has made huge strides in the US and Western Europe, but this progress is only apparent in the junior levels of the workplace. This book shows how mentoring women entrepreneurs and women managers provides the key that opens the door to the new economy. Understand why mentoring is key to women's economic advancement Learn how mentoring yields tangible benefits beyond the workplace Delve into the experiences of real mentor/mentee pairs Consider the effectiveness of various types of mentoring Despite the increasing opportunities for women in business, statistics and pervading stereotypes suggest that true gender equality is still far on the horizon. Mentoring and sponsorship can be tremendously helpful to women looking to achieve great things—the wisdom of experience is a powerful asset in business strategy and decision-making, and the mentor/mentee relationship benefits everyone. Breaking Through makes a compelling case for the effectiveness of mentoring, with real women's stories of success"--